Theileria parva genomics reveals an atypical apicomplexan genome - Nene, Vishvanath M.; Bishop, Richard P.; Morzaria, S.P.; Gardner, M.J.; Sugimoto, C.; Ole-MoiYoi, O.K.; Fraser, C.M.; Irvin, A. (Elsevier, 2000)
The discipline of genomics is setting new paradigms in research approaches to resolving problems in human and animal health. We propose to determine the genome sequence of Theileria parva, a pathogen of cattle, using the random shotgun approach pioneered at The Institute for Genomic Research (TIGR). A number of features of the T. parva genome make it particularly suitable for this approach. The G+C content of genomic DNA is about 31 percent, non-coding repetitive DNA constitute less than 1 percent of total DNA and a framework for the 10-12 Mbp genome is available in the form of a physical map for all four chromosomes. Minisatellite sequences are the only dispersed repetitive sequences identified so far, but they are limited in distribution to 13 of 33 SfiI fragments. Telomere and sub-telomeric non-coding sequences occupy less than 10 kbp at each chromosomal end and there are only two units encoding cytoplasmic rRNAs. Three sets of distinct multicopy sequences encoding ORFs have been identified but it is not known if these are associated with expression of parasite antigenic diversity. Protein coding genes exhibit a bias in codon usage and introns when present are unusually short. Like other apicomplexan organisms, T. parva contains two extrachromosomal DNAs, a mitochondrial DNA and a plastid DNA molecule. By annotating the gnome sequence, in combination with the use of microarray technology and comparative genomics, we expect to gain significant insights into unique aspects of the biology of T. parva. We believe that the data will underpin future research to aid in the identification of targets of protective CD8 + cell mediated immune responses, and parasite molecules involved in inducing reversible host leukocyte transformation and tumour-like behaviour of transformed parasitised cells.